2019
DOI: 10.1002/mus.26401
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative myotonia assessment with a commercially available dynamometer in myotonic dystrophy types 1 and 2

Abstract: Introduction: The objective of this study was to develop a simple method for quantitative assessment of myotonia in patients with myotonic dystrophy type 1 (DM1) and DM2, to compare the myotonia severity, and to correlate this objective outcome with a subjective scale, the Myotonia Behaviour Scale (MBS). Methods: A commercially available dynamometer was used for all measurements. The relaxation time after voluntary contraction was measured in 20 patients with DM1, 25 patients with DM2, and 35 healthy controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…The MBS scale was developed for patients with myotonia congenita, who mostly show a severer grip myotonia in comparison to DM2 (22). In a recently published study, MBS has been adopted also in DM1 and DM2 patients to validate the relaxation time on a dynamometer as measurement of myotonia (23). The results of our study were similar to those recently published by Horakova et al as we found a mean MBS score of 1.5 (vs. Horakova 1.6).…”
Section: Discussionsupporting
confidence: 89%
“…The MBS scale was developed for patients with myotonia congenita, who mostly show a severer grip myotonia in comparison to DM2 (22). In a recently published study, MBS has been adopted also in DM1 and DM2 patients to validate the relaxation time on a dynamometer as measurement of myotonia (23). The results of our study were similar to those recently published by Horakova et al as we found a mean MBS score of 1.5 (vs. Horakova 1.6).…”
Section: Discussionsupporting
confidence: 89%
“…The software is commercially licensed, specific to the force transducer and does not allow modifications to include other measures for example, audio commands. Other approaches using dynamometry or a sensor glove either showed poor repeatability or did not measure grip force time series and the warm-up typical of myotonia [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%